Pemerintahan Kristus Selama Seribu Tahun Di Dunia (Wahyu 20:1-15) - Lanny Laras Tumbel (Sekolah Tinggi Teologi Injili Indonesia Surabaya, 2016)
The Millennium Age (1000 year reign of Christ on the earth( is a subject that not many Endtime authors speak about. But this is a time period that deserves to be addressed. During the Millennial Age, Satan will be bound and out of action until the end of time. The agent that binds Satan is an angel. The duration of this confinement will be a thousand years. The purpose for this confinement is so that he will no longer be able to deceive the nations. However, at the end of that period he will be loosed “a little season.” After the Great Tribulation, that is the worst seven years the world will ever know will follow The Millennium Age, which will be considered the greatest time period the world will ever know. This will be a very prosperous time period in which humans will live hundreds of years. Those who die at hundred years will be considered dying prematurely. Wild animals, considered dangerous man eaters, will be led around by children. Everyone will know the Lord.